Impact of functional disability on lifestyle for patients with arthritis - ali, mohammed (Iraqi National Journal of Nursing Specialties, 2005)
A descriptive study, which was using an assessment approach, was conducted for the determination of the impact of rheumatoid arthritis and osteoarthritis patient’s functional disability upon their life style. The study was carried out at the Rheumatology and outpatients clinics of ALKarama Teaching Hospital, Baghdad Teaching Hospital AL-Kindey Teaching Hospital and Specialized surgeries Teaching Hospital for the period of October 15th 2003 through May 13th 2004 in Baghdad City. A purposive (non-probability) sample of (245) arthritis patients which was comprised (111) rheumatoid arthritis patients and (134) osteoarthritis patients, was selected out of the early stated settings. The questionnaire was comprised of two main parts. Part one dealing with sociodemographical data like (age, sex, marital status, education level) and part two was including lifestyle domains of physical, occupation, social, environmental emotional and spiritual. The findings of the study presented that these patients functional disability had great impact upon their lifestyle with regard to their daily living activities, such as dressing, cleaning, walking and working, as well as the domains of family interaction, environmental interaction and emotional disorders. The study recommended that well designed and structured health education program can be presented to these patients with respect to preventive, curative and rehabilitative issues by which complications can be reduced and health status can be promoted and maintained through the exercise program, drugs montoring and follow-up and patients education about the disease and drugs side effects.